Insight into enzymatic nitrile reduction : QM/MM study of the catalytic mechanism of QueF nitrile reductase - Ribeiro, António J. M. (2015)
The NADPH-dependent QueF nitrile reductases catalyze the unprecedented four-electron reduction of nitrile to amine. QueF nitrile reductases can be found in the tRNA biosynthetic pathway of many bacteria and are potential antimicrobial drug targets. QueF enzymes have also attracted great attention as potential industrial biocatalysts for replacing the nitrile-reducing metal hydride catalysts used commonly in the chemical and pharmaceutical industries. Because of their narrow substrate specificity, engineering of the QueF enzymes to generate variants with altered or broadened substrate specificity is crucial for producing practically useful biocatalysts. A better understanding of the catalytic mechanism of the QueF enzymes would expedite rational inhibitor design and enzyme engineering. In this work, we probed the catalytic mechanism of the Vibrio cholerae QueF nitrile reductase by state of the art QM/MM calculations at the ONIOM(B3LYP/6-311+G(2d,2p):AMBER) level. The QM/MM computational results suggest that the nitrile to amine conversion proceeds through four major stages: (a) formation of a C–S covalent bond between the substrate and the catalytic cysteine residue to form the thioimidate intermediate, (b) hydride transfer from NADPH to the substrate to generate the thiohemiaminal intermediate, (c) cleavage of the C–S covalent bond to generate the imine intermediate, and (d) second hydride transfer from NADPH to the imine intermediate to generate the final amine product. The free energy barrier for the rate-limiting step, i.e. the second hydride transfer, was found to be 20.8 kcal/mol. The calculated barrier height and the catalytic residues identified as essential for nitrile reduction are in accordance with the currently available experimental data. The knowledge about the transition states, intermediates, and protein conformational changes along the reaction path will be valuable for the design of enzyme inhibitors as well as the engineering of QueF nitrile reductases.